SOCIO-PHILOSOPHICAL ANALYSIS OF HUMAN DEATH: INTERPRETATION OF CLINICAL AND BIOLOGICAL DEATH - ugli, Khudayberganov Ravshonbek Khudaybergan (International Journal of Psychosocial Rehabilitation, 2020)
Human death requires understanding from various points of view in order to identify its role, functions and axiological significance in the life of society and a specific person, to develop certain norms of behavior before the fact of the inevitability and inexorability of death. It is these qualities and properties that give a special shade to the "taste" of life that determine interest in this phenomenon and testify in favor of the theoretical and applied significance of the problem. This article is written with the aim of: establishing the main approaches to the interpretation of the role of death in society and to identify the features of public consciousness in various cultures associated with the interpretation of death; to systematize and characterize ethical standards that have arisen as a result of understanding the inevitability of death, and to develop recommendations for people employed in the field of education and in need of a pedagogical understanding of this phenomenon. In particular, tasks were set as: to consider the role and place of death among the main phenomena that determine the existence of a person, to establish the features of the approaches developed by philosophical thought in comprehending death and near-death phenomena; to analyze the genesis and evolution of ideas about death in the mythical and epic heritage of peoples and the ways in which public consciousness sought to resolve the dilemma "life gives rise to death"; to investigate modern ideas about death and identify the main trends in its interpretation, which have formed in the public consciousness; identify a set of factors leading to the loss of purpose and meaning of life; to show that suicide and euthanasia are human weaknesses that the individual should not resort to even in the most desperate situation; to investigate the process of entering a person’s fear of death, the evolution of this feeling depending on age characteristics, to identify crisis stages in an individual’s life leading to destructive behavior, to develop recommendations for teachers, parents and other interested parties on the prevention of necrophilic behavior.